Perylenetetracarboxy-3, 4:9, 10-diimide derivatives with large two-photon absorption activity. (8th January 2019) - Garoni, Eleonora; Nisic, Filippo; Colombo, Alessia; Fantacci, Simona; Griffini, Gianmarco; Kamada, Kenji; Roberto, Dominique; Dragonetti, Claudia
Abstract : Perylenetetracarboxy-3, 4:9, 10-diimides with large TPA cross-sections. Abstract : Three new perylenetetracarboxy-3, 4:9, 10-diimides, bearing 2, 6-diisopropylphenyl groups at the imide positions and 4-(R-ethynyl)phenoxy moieties (R = 4, 7-di(2-thienyl)benzo[ c ][1, 2, 5]thiadiazole (P2 ), pyrene (P3 ) or pyrene-CH2 OCH2 (P4 )) at the four bay positions, were prepared, along with the known related derivative (R = phenyl (P1 )), and well characterized. They have large two-photon absorption (TPA) cross-sections ( σ 2 ), as determined by the Z-scan technique, the highest values being reached withP2 which bears a planar π-delocalized donor moiety.P3 is characterized by higher σ 2 values than bothP1, as expected for the higher π-conjugation of the donor pyrene moiety with respect to phenyl, andP4, due to the presence of the flexible and non-conjugated CH2 OCH2 bridge between the pyrene and the ethynyl fragment in the latter compound. The molecular geometry ofP1–P4 has been optimized by DFT modeling, showing that inP2 andP3 the bay substituents are stacked due to the π–π interactions of both pyrene and thiophene groups. The LUMO ofP1–P4 lies at the same energy and is essentially delocalized on the perylene core whereas the HOMO and HOMO−1 of bothP2 andP3 are degenerate and do not show contribution from the perylene core contrarily to that ofP1 andP4 . The HOMO–LUMO gap is therefore essentially influenced by the HOMO which reflects the electronic charge delocalization on the bay substituents, the lower gaps being observed forP2 andP3, which are characterized by the best TPA properties.